PENGARUH PELATIHAN (BASIC TRANING) DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. TELKOM BIMA - Febriantisari, Delia; Wulandari, Wulandari; Kusumayadi, Firmansyah (Journal MISSY (Management and Business Strategy), 2022)
Employee performance is always related to several elements such as: knowledge, skills, attitudes, and competencies possessed by employees. It is certain that competent employees will have high performance. Every company wants each of its employees to have competencies in accordance with their duties, so that employees can meet the assigned task standards. Producing competent employees in accordance with their duties and positions is a problem that is not easily solved by the company's human resource management. The problems in this research will be answered with quantitative data collected through questionnaires. Before the questionnaire data is analyzed to answer research problems, the researcher will first conduct tests related to the validity of the instrument and the reliability of the measurement results of the instrument. Based on the results of the research data analysis, several conclusions can be obtained in this study. The conclusions obtained are the answers to the problem formulation and research hypotheses that have been proposed. The following are the conclusions of the study, including: (1) Training (basic training) has a positive and partially significant effect on the performance of employees of PT. Telkom Bima, (2) Motivation has a positive and partially significant effect on the performance of employees of PT. Telkom Bima, and (3) Training (basic training) and motivation have a positive and significant effect on simultaneously the performance of employees of PT. Telkom Bima.